THE EFFECT OF INTEGRATION OF PROBLEM BASED LEARNING (PBL) LEARNING MODELS AND ORIENTATION, IDENTIFY, DISCUSSION, DECISSION AND ENGAGE IN BEHAVIOR (OIDDE) TO SOCIO-SCIENTIFIC DECISION MAKING SKILLS STUDENTS AT SMP NEGERI 2 BITUNG - Kaliboto, Bellatrix H.Ch; Sumampouw, Herry; Tumbel, Ferny M. (PT. Antis International Publisher, 2024)
This research uses a hypothesis test of one-way analysis of covariance or one-way ANCOVA to measure the respective effects of using the integration of the PBL model with OIDDE on socioscientific decision making skills. Before testing the hypothesis, prerequisite tests must be carried out, namely the normality test and homogeneity test. The use of this test is assisted by SPSS 23 for Windows software. The conclusion of this research is that the integration of the Problem Based Learning (PBL) learning model with the OIDDE (Orientation, Identify, Discussion, Decision, and Engage In Behavior) learning model has a real influence on improving students' Socioscientific Decision Making skills with a sig. 0.001 > 0.005 and the highest corrected mean value was 86.21